1997
DOI: 10.1051/kmae:1997002
|View full text |Cite
|
Sign up to set email alerts
|

Données récentes sur les caractéristiques morphologiques et biologiques de la population d'Alose feinte du Rhône (Alosa fallax rhodanensis Roule, 1924)

Abstract: Les caractéristiques morphologiques et biologiques de la population actuelle d'Alose feinte du Rhône (Alosa fallax rhodanensis) sont présentées. Elles sont analysées à partir d'un lot de 1479 adultes capturés (pêche au filet) lors de leur migration anadrome au cours de trois années.Les critères morphologiques utilisés (notamment le nombre de branchiospines) et leur faible variabilité individuelle ne font apparaître qu'un seul taxon, identifié comme étant celui d'Alosa fallax rhodanensis.La longueur moyenne (Lf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
6
0
5
Order By: Relevance
“…It takes place well before temperatures drop to below 19°C (CLARIDGE and GARDNER, 1978 ;O'LEARY and KYNARD, 1986) as has been found elsewhere LIMBURG (1996) with the American shad in the Hudson River. It is likely that this earliness is explained by the spawning grounds of Saxy on the Rhône being close (LE CORRE et al, 1997 ;LEBEL et al, 1999), about 7 km upstream of the town of Arles and about 30 km upstream of the pumps at Le Sambuc, and 55 km from the mouth of the Rhône. APRAHAMIAN (1988) suggested that juveniles migrate close to the shore, which would explain why they are readily taken up by the pumps in June-July, when they are still small.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It takes place well before temperatures drop to below 19°C (CLARIDGE and GARDNER, 1978 ;O'LEARY and KYNARD, 1986) as has been found elsewhere LIMBURG (1996) with the American shad in the Hudson River. It is likely that this earliness is explained by the spawning grounds of Saxy on the Rhône being close (LE CORRE et al, 1997 ;LEBEL et al, 1999), about 7 km upstream of the town of Arles and about 30 km upstream of the pumps at Le Sambuc, and 55 km from the mouth of the Rhône. APRAHAMIAN (1988) suggested that juveniles migrate close to the shore, which would explain why they are readily taken up by the pumps in June-July, when they are still small.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of the subspecies is still debatable, although it is certainly the twaite shad (LE CORRE et al, 1998). There have been several studies on this species, dealing with its taxonomy, status, migrations and its biology (RAMEYE et al, 1976 ;QUIGNARD and KARTAS, 1977 ;DOUCHEMENT, 1981 ;QUIGNARD and DOUCHEMENT, 1991 ;LE CORRE et al, 1997). Although the biology and ecology of spawning shad in the Rhône is well known (LE CORRE et al, 1997) practically nothing is known about the migration and the growth of young of the year in this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cependant, dans un affluent de ce dernier fleuve (rivière Zézère), elle est trouvée sous une forme lacustre (non amphihaline) suite à la création d'un barrage (Castelo de Bode) à son embouchure avec le Tage, il y a une quarantaine d'années (ALEXANDRINO, 1996). Enfin, la grande alose, considérée comme rare sur la façade méditerranéenne française (ROULE, 1924) mais introduite dans le Rhône à partir de la Dordogne dans le milieu de ce siècle (HOESTLANDT, 1958) paraît avoir totalement disparu de ce fleuve aujourd'hui (LE CORRE et al, 1997).…”
Section: Présentation Des Cours D'eau Et Des Populations D'aloses Anaunclassified
“…Among all of the fish populations present, migrating fish were the most seriously affected. The shad (Alosa fallax rhodanensis) stock, the target species for the Rhône restoration program (Le Corre et al, 1997), decreased drastically, from 50 tons fished in the 1920's to less than 7 tons at present. The shad did not totally disappear, as 'substitute' spawning grounds appeared downstream of the first dam.…”
Section: Introductionmentioning
confidence: 99%